Analisis Pengendalian Kualitas Produk Kopi Kutjur Menggunakan Metode New Seven Tools di UD. Sampun Slamet - Irianto, Oktavyan Dwi; Hendrarini, Hamidah; Indah, Pawana Nur (Universitas Galuh, 2025)
The contemporary business landscape is marked by heightened competition, necessitating comprehensive enhancements across various facets, particularly the quality of products offered. Quality stands out as a pivotal determinant in captivating consumer preference and product selection. Kopi Kutjur UD. Sampun Slamet specializes in the production of powdered coffee and coffee beans, which may occasionally exhibit imperfections or damage without detailed documentation. This study seeks to achieve three primary objectives: (1) scrutinize the implementation of coffee bean quality control practices at Kopi Kutjur UD. Sampun Slamet; (2) assess the extent of product damage in coffee beans within the aforementioned establishment; and (3) analyze the efficacy of the New Seven Tools methodology in mitigating coffee product damage and imperfections during the production process. The research methodology relies on the New Seven Tools approach, revealing that factors contributing to damage include Man, Machine, Method, and Material. Recommendations include the implementation of a Checksheet to systematically record coffee bean product damages.